The outcomes of ultrasonic and laser therapy in case of temporomandibular disorders – an evidence based update - NEGUCIOIU Marius; KUI Andreea; MITARIU Mihai; MANZIUC Manuela; CONDOR Daniela; MITARIU Loredana; BUDURU Smaranda (Balneo and PRM Research Journal, 2021)
Introduction. Temporomandibular disorders (TMDs) are considered multifactorial conditions, thereby with different therapy options, from occlusal equilibration, splint therapy, pharmacotherapy or physical therapy. Among the physical therapies, over the last years, laser therapy and ultrasound therapy have gained attention, as different experimental or clinical studies suggest their efficacy in case of TMDs. The aim of our literature review is to evaluate the available evidence on the effectiveness of laser and ultrasound therapy in the treatment of temporomandibular disorders. Material and method. A research of literature has been performed - articles published over the last 5 years (January 2016 until June 2021) were searched by introducing a combination of different terms, using the Pubmed, Scopus and Google Scholar databases. Results and discussions. A total number of 332 articles was found. For multiple publications regarding the same group of patients, the most recent studies were included. Initial analysis of titles and abstracts eliminated 232 articles, leaving 35 articles whose full text was examined. 20 articles met the inclusion criteria Conclusions. According to the findings of this literature update we can conclude that low level laser therapy, ultrasound therapy, and photobiomodulation may effectively reduce pain for patients suffering of muscular and joint TMDs. However, their effects appear to be only shortly maintained, and only for less complex cases. In addition, it was difficult to compare the studies included, as they do not offer an optimal usage (program, duration of sessions, or number of sessions) of each technique. In this context, we consider that further randomized clinical studies are necessarily to compare each physical technique as well as their synergic effect on the symptoms in case of temporomandibular disorders.